Family and Adolescent Values Practice in School Environment - Chunga Romero, Deidal; Olmedo Zambrano Santos, Roberth (International Journal of Psychosocial Rehabilitation, 2020)
Values are the essential basis on which social life is based. The family is the basic core of society, resulting in the primary reference in the formation of values of human beings. Education generates the indispensable conditions for people to realize their fundamental rights and acquired capacities, consolidating the practice of values as a key process in the formation of future generations. In Ecuador, the issue of values is a fundamental axis of public policy, so valuable time and important resources are devoted to the formation and practice of values for citizens from an early age. The objective of the research is to determine the impact of the values of adolescents in the school environment in the XXI Century Educational Unit Blanca Cuadros de Zambrano, located in the Rocafuerte canton of the province of Manabí. The methodology used was qualitative and quantitative, for which a bibliographic review of articles, books, book chapters, laws, regulations, manuals and other academic documents related to the role of the family and the practice of values was carried out. of teenagers. It was verified that the low practice of values in students causes problems in academic performance.